Survival Rate and Deformation of External Hexagon Implants with One-Piece Zirconia Crowns - Bottino, Marco Antonio [UNESP]; Oliveira, Flavio Rosa de [UNESP]; Sabino, Clarice Ferreira [UNESP]; Dinato, Jose Cicero [UNESP]; Silva-Concilio, Lais Regiane; Tribst, Joao Paulo Mendes (Mdpi, 2021)
This study aimed to evaluate the survival rates of several external hexagon implants directly connected to zirconia crowns after thermomechanical fatigue. The deformation of the hexagons and the integrity of zirconia crowns were also evaluated. A monolithic zirconia crown (Y-TZP) and four different external hexagon dental implants (n = 10, N = 40) were mounted together and embedded in polyurethane. The specimens were subjected to thermomechanical cycling for 2.5 x 10(6) cycles, at 3.0 Hz frequency, at 200 N loading. The interface of the implant/zirconia crown system, zirconia crowns integrity before and after cycling, and the implant hexagon surface were evaluated under stereomicroscopy and SEM. A nanohardness analysis was performed to verify the hardness of zirconia and implants. Statistical analysis was performed using the Kaplan-Meier test, Multi-Sample Survival Tests, Logrank Test, (p = 0.05). The data did not show significant differences in the survival rates of different implant groups. However, some crowns presented fractures (16.67%) and the external hexagon region of the implants presented plastic deformations (100%). During chewing simulation, the interface between titanium implant and zirconia abutment can promote plastic deformation in the metal and surface defects in the ceramic. In addition, the types of interface defects can be affected by the external hexagon design.
Keywords: dental implants; dental materials; zirconia; dental ceramics; biomechanics